2015
DOI: 10.3126/kumj.v11i4.12525
|View full text |Cite
|
Sign up to set email alerts
|

The Correlation Between Fine Needle Aspiration Cytology and Histopathology of Head and Neck Lesions in Kathmandu University Hospital

Abstract: Background Fine needle aspiration cytology (FNAC) with it’s minimally invasiveness has been a well accepted procedure in the initial diagnosis of various swellings. With time and experience high sensitivity and specificity of FNAC over conventional open biopsy has lead to the wide acceptance of this procedure.Objective To evaluate the utility of aspiration cytology as a first-line diagnostic tool in palpable head and neck masses and correlate with histologic results for evaluating diagnostic accuracy.Methods A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 13 publications
2
20
1
Order By: Relevance
“…Rathod et al and Rajbhandari et al observed similar findings with maximum incidence of colloid goiter and then papillary carcinoma. 6,9 A study by Singal et al reported colloid goiter as the most commonly observed disorder in thyroid region similar to our finding. 10 Rout et al found colloid goiter as the most common among thyroid swelling followed by colloid goiter with cystic degeneration.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Rathod et al and Rajbhandari et al observed similar findings with maximum incidence of colloid goiter and then papillary carcinoma. 6,9 A study by Singal et al reported colloid goiter as the most commonly observed disorder in thyroid region similar to our finding. 10 Rout et al found colloid goiter as the most common among thyroid swelling followed by colloid goiter with cystic degeneration.…”
Section: Discussionsupporting
confidence: 91%
“…Other studies observed reactive lymphadenitis as the most common diagnosis of lymph node similar to our study. [9][10][11] In contrast, few studies showed tubercular lymphadenitis was the most frequent finding among lymph nodes. 1,2,[5][6][7] Out of 66 cases were available for HPE, NHL (27.3%) was the commonest pathological findings followed by granulomatous lymphadenitis (25.8%), metastatic carcinoma (19.7%), reactive lymphadenitis (10.6%), HL (7.6%), Kikuchi fujimoto disease (4.5%) and abscess (4.5%).…”
Section: Discussionmentioning
confidence: 97%
“…False negative cases may be explained by degenerative changes or the intensity of inflammation or hemorrhage leading to misinterpretation . The presence of a mixed population of lymphoid tissues and tingible body macrophages suggest reactive lymphoid hyperplasia but don't definitively rule out lymphomas or other malignancies . FNAC has been proved to be a reliable diagnostic tool in the detection of lymph node malignancies with good sensitivity and specificity as demonstrated by our study.…”
Section: Discussionmentioning
confidence: 68%
“…8,9 The whole spectrum of biopsied head and neck lesions include a variety of differential diagnosis ranging from 10 In the present study, a total of 145 cases were analysed.…”
Section: Discussionmentioning
confidence: 99%